A dialética exclusão/inclusão e os estudantes trabalhadores do ensino médio em situação de pobreza - Nogueira, Carlos Gutyerrez Moreno (2023)
Education is a social and fundamental human right guaranteed by the Federal Constitution. However, this right has been violated over the years, especially for secondary school students. In Brazil, secondary education has gone through moments of identity crisis, in the sense of not knowing exactly what its purpose is. Currently, in public schools, this segment is made up of students who reconcile the difficulties of the school and work routine. In this sense, the starting question of this research is: How are processes of exclusion experienced by working high school students living in poverty? And general objective: To understand how the processes of exclusion are experienced by working high school students living in poverty. The methodology used was qualitative research, with semi-structured interviews with high school students at the EEMTI Prof. Antônio Martins Filho State School located in the municipality of Maracanaú in Ceará. Seven interviews were carried out, three with men and four with women. The material was analyzed using Bardin's content analysis and Atlas ti 5.2. The results of the research show that the experience of school and work is seen as a possibility of achieving a better future; reconciling work and school creates numerous difficulties, but it is also seen as a possibility of overcoming poverty. We also observed that a reality like this is also marked by students returning to school after years away. It was also identified that the experience of a trans woman at school encompasses other forms of exclusion and that this also applies to black students who constantly suffer prejudice because of their color. The experience of exclusion is crossed by inclusion, where students are included in the school system, but find it difficult to really stay.